2009
DOI: 10.1021/jp908397w
|View full text |Cite
|
Sign up to set email alerts
|

NaSc(BH4)4: A Novel Scandium-Based Borohydride

Abstract: A new alkaline transition-metal borohydride, NaSc(BH 4 ) 4 , is presented. The compound has been studied using a combination of in situ synchrotron radiation powder X-ray diffraction, thermal analysis, and vibrational and NMR spectroscopy. NaSc(BH 4 ) 4 forms at ambient conditions in ball-milled mixtures of sodium borohydride and ScCl 3 . A new ternary chloride Na 3 ScCl 6 (P2 1 /n, a ) 6.7375), isostructural to Na 3 TiCl 6 , was identified as an additional phase in all samples. This indicates that the formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 136 publications
(69 citation statements)
references
References 37 publications
2
67
0
Order By: Relevance
“…The reaction between KBH 4 and K 3 ScCl 6 observed by in situ SR-PXD corresponds well with the mass loss and thermal events observed in TGA and DSC between 510 and 590 K. Formation of a solid solution was also observed recently during decomposition of NaSc(BH 4 ) 4 . 25 Furthermore, fast dissolution (within minutes) of LiCl in LiBH 4 was observed at 383 K < T < 523 K and relatively slow segregation of LiCl from the solid solution Li(BH 4 ) 1-x Cl x at RT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction between KBH 4 and K 3 ScCl 6 observed by in situ SR-PXD corresponds well with the mass loss and thermal events observed in TGA and DSC between 510 and 590 K. Formation of a solid solution was also observed recently during decomposition of NaSc(BH 4 ) 4 . 25 Furthermore, fast dissolution (within minutes) of LiCl in LiBH 4 was observed at 383 K < T < 523 K and relatively slow segregation of LiCl from the solid solution Li(BH 4 ) 1-x Cl x at RT.…”
Section: Resultsmentioning
confidence: 99%
“…24,25 Here, we report on the synthesis, crystal structure, hydrogen desorption properties, and Raman, infrared, and NMR spectra of another scandium-based bimetallic borohydride, KSc(BH 4 ) 4 .…”
Section: ) 4 ]mentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental data are taken from Ref. 12. For these materials, PBE calculations predict very low-density structures to be thermodynamically stable while, at the same time, produce large deviations when optimizing their complicated experimental structures.…”
Section: Effects Of Exchange-correlation Functionals and Vdw Intmentioning
confidence: 99%
“…12 Details on these decomposition steps have not been experimentally determined yet. 12 Soon after the experimental synthesis of NaSc(BH 4 ) 4 , several theoretical studies were carried out. Huang et al 13 reported that the Cmcm phase of NaSc(BH 4 ) 4 is an insulator with a band gap of E g = 5.055 eV.…”
Section: Introductionmentioning
confidence: 99%